The Influence of Reliability on Customer Loyalty Mediated by Customer Satisfaction - Rizkina, Ayuni Kurnia Agung; Zakaria, Zakaria; Labo, Irwan Adam (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to examine the effect of reliability on customer satisfaction and loyalty at the Hendrikus Tax Consulting Office in Jayapura, with customer satisfaction acting as a mediator. The primary hypothesis posits that service reliability enhances customer satisfaction, boosting customer loyalty. Research Design and Methodology: The research employs a quantitative survey method, collecting data through questionnaires distributed to 97 purposively sample respondents from the office's client base. Data analysis was conducted using SmartPLS version 4, evaluating measurement and structural models to test validity, reliability, and hypotheses. Findings and Discussion: The results indicate that service reliability positively and significantly affects customer satisfaction (t-statistic 8.042, p-value 0.000) and customer loyalty (t-statistic 1.986, p-value 0.048). Customer satisfaction substantially mediates the relationship between reliability and loyalty (t-statistic 4.969, p-value 0.000). Implications: These findings suggest that enhancing service reliability can improve customer satisfaction and loyalty, which is crucial for service strategy in tax consulting. The study also highlights the need for further research into other factors influencing customer satisfaction and loyalty in different service industries.